Aerosol Optical Depth Over India. Issue 7 (13th April 2018) - David, Liji Mary; Ravishankara, A. R.; Kodros, John K.; Venkataraman, Chandra; Sadavarte, Pankaj; Pierce, Jeffrey R.; Chaliyakunnel, Sreelekha; Millet, Dylan B.
Abstract: Tropospheric aerosol optical depth (AOD) over India was simulated by Goddard Earth Observing System (GEOS)‐Chem, a global 3‐D chemical‐transport model, using SMOG (Speciated Multi‐pOllutant Generator from Indian Institute of Technology Bombay) and GEOS‐Chem (GC) (current inventories used in the GEOS‐Chem model) inventories for 2012. The simulated AODs were ~80% (SMOG) and 60% (GC) of those measured by the satellites (Moderate Resolution Imaging Spectroradiometer and Multi‐angle Imaging SpectroRadiometer). There is no strong seasonal variation in AOD over India. The peak AOD values are observed/simulated during summer. The simulated AOD using SMOG inventory has particulate black and organic carbon AOD higher by a factor ~5 and 3, respectively, compared to GC inventory. The model underpredicted coarse‐mode AOD but agreed for fine‐mode AOD with Aerosol Robotic Network data. It captured dust only over Western India, which is a desert, and not elsewhere, probably due to inaccurate dust transport and/or noninclusion of other dust sources. The calculated AOD, after dust correction, showed the general features in its observed spatial variation. Highest AOD values were observed over the Indo‐Gangetic Plain followed by Central and Southern India with lowest values in Northern India. Transport of aerosols from Indo‐Gangetic Plain and Central India into Eastern India, where emissions are low, is significant. The major contributors to total AOD over India are inorganic aerosol (41–64%), organic carbon (14–26%), and dust (7–32%). AOD over most regions of India is a factor of 5 or higher than over the United States. Plain Language Summary: Overhead amounts of particulate matter, their chemical make up, and their variations over India, a highly polluted and fast developing country, were calculated using a global model. It shows that the particulate pollution levels over the Indo‐Gangetic Plain is more than 5 times higher than over the United States. The use of the most recent available emission inventory shows that there is more black carbon, from incomplete combustion, than estimated using the existing regional inventory. The calculations also show that the cleanest part is the very Northern India and that pollution over Eastern India is significantly influenced by what happens over the Indo‐Gangetic Plain. Key Points: Aerosol optical depth over India is calculated and compared with observations (satellite and AERONET) Model reproduces the observed fine mode aerosols; the composition of the aerosols shows importance of black carbon and dust over India The Indo‐Gangetic Plain is the most polluted region over India, and this region control aerosols over Eastern India